PeruCRIS: Scope and progress in the implementation of the first release of the Peruvian CRIS platform - Córdova Yamauchi, Claudia Gysella (2022)
Previous presentations of the PerúCRIS project for developing a national CRIS in Peru held at various euroCRIS events have shown the scope and the aims of this initiative based on an open source solution. Now, as this national platform approaches its release in production, a summary is provided of the PerúCRIS project achievements, its various ongoing worklines and its pending steps and future plans. The expectation is for the first modules of the platform to be released in July 2022 at https://perucris.pe. Some emphasis is made on the system interoperability pilots between the national platform and a number of institutional CRIS in Peru based on both DSpace-CRIS and Pure.